An extensively drug-resistant Pseudomonas aeruginosa isolate from Myanmar - Thanda Tun; Sakiusa Cabe Baleivanualala; Mareike Britta Erdmann; Gregory Gimenez; Htin Lin Aung (Journal of Global Antimicrobial Resistance, 2024)
ABSTRACT: Objectives: Antimicrobial resistance (AMR) including multidrug-resistant (MDR) and extensively drug-resistant (XDR) Pseudomonas aeruginosa has emerged as one of the serious public health threats across the globe. Southeast Asia is a ‘hot spot’ of antimicrobial-resistant bacteria, including MDR P. aeruginosa. Despite Myanmar being located in Southeast Asia and suffering from a high infectious disease burden, data on MDR and XDR P. aeruginosa from Myanmar are limited. In this communication, we report the draft genome of an XDR P. aeruginosa isolate, MMXDRPA001, that was identified during a routine diagnosis in Myanmar. Methods: An MMXDRPA001 isolate colonising a hospitalised patient was characterised by antibiotic resistance profiling following standard methods and whole-genome sequencing using an Illumina MiSeq platform. The generated reads were de novo assembled using SPAdes (v.3.9.1). Annotation was performed by Prokka (v.1.14.0). Sequence type, antimicrobial resistance and virulence-related genes were predicted from the sequence. The phylogenetic relationships of all P. aeruginosa isolates were determined using core genome single-nucleotide polymorphisms (SNPs) analysis utilising Snippy (v.4.6.0) and Gubbins (v.2.3.4). Results: P. aeruginosa MMXDRPA001 was resistant to most antipseudomonal β-lactams, aminoglycosides and quinolones. The assembly comprised 145 contigs totalling 6 808 493 bases of sequence and a total of 6183 coding sequences. The isolate belonged to sequence type (ST) 235, contained carbapenemase-encoding gene blaIMP-1 and was clonally related to a previously reported isolate from Thailand. Conclusion: The identification of an international high-risk clone of ST235 XDR isolate in Myanmar, genomically relating to that from a neighbouring country underscores the need for coordinated AMR surveillance throughout healthcare settings in Myanmar and in the Southeast Asia region.